Cognitive dysfunction in lower motor neuron disease: executive and memory deficits in progressive muscular atrophy. Issue 2 (18th June 2010) - Raaphorst, Joost; de Visser, Marianne; van Tol, Marie-José; Linssen, Wim H J P; van der Kooi, Anneke J; de Haan, Rob J; van den Berg, Leonard H; Schmand, Ben
Abstract : Aim: In contrast with findings in amyotrophic lateral sclerosis (ALS), cognitive impairments have as yet not been shown in the lower motor neuron variant of motor neuron disease, progressive spinal muscular atrophy (PMA). The objective of this study was to investigate cognitive function in PMA and to compare the cognitive profile with that of ALS. In addition, visuospatial functions were assessed comprehensively; these tests are underrepresented in earlier neuropsychological investigations in ALS. Methods: 23 PMA and 30 ALS patients (vital capacity >70% of predicted value) underwent a neuropsychological assessment adapted to motor impairments: global cognitive and executive functioning, psychomotor speed, memory, language, attention and visuospatial skills. The results were compared with age, education and sex matched controls and with normative data. Results: Compared with controls, PMA patients performed worse on attention/working memory (digit span backward), category fluency and the Mini-Mental State Examination. Compared with normative data, PMA patients most frequently showed impairment on three measures: letter–number sequencing, and immediate and delayed story recall. 17% of PMA patients showed cognitive impairment, defined as performance below 2 SDs from the mean of normative data on at least three neuropsychological tests. In ALS, similar but more extensive cognitive deficits were found. Visuospatial dysfunction was not found in PMA and ALS. Conclusions: 17% of PMA patients have executive and memory impairments. PMA with cognitive impairment adds a formerly unknown phenotype to the existing classification of motor neuron diseases.